From natural products to HDAC inhibitors: An overview of drug discovery and design strategy. (15th December 2021) - Qiu, Xiang; Zhu, Lv; Wang, Huan; Tan, Yan; Yang, Zhuang; Yang, Linyu; Wan, Li
Graphical abstract: Highlights: Drug discovery of natural HDAC inhibitors including isolation and total synthesis. Examples of structural modification of natural HDAC inhibitors. Different design strategies of naturally occurring HDAC inhibitors. Summary of in vitro and in vivo activity of active compounds. Abstract: Histone deacetylases (HDACs) play a key role in the homeostasis of protein acetylation in histones and have recently emerged as a therapeutic target for numerous diseases. The inhibition of HDACs may block angiogenesis, arrest cell growth, and lead to differentiation and apoptosis in tumour cells. Thus, HDAC inhibitors (HDACi) have received increasing attention and many of which are developed from natural sources. In the past few decades, naturally occurring HDACi have been identified to have potent anticancer activities, some of which have demonstrated promising therapeutic effects on haematological malignancies. In this review, we summarized the discovery and modification of HDAC inhibitors from natural sources, novel drug design that uses natural products as parent nuclei, and dual target design strategies that combine HDAC with non-HDAC targets.